Trends in the initial management of severe preeclampsia and eclampsia in Indonesia: A medical record study (2018–2021) - Pratiwi, Ratih; Indriyani, Indriyani; Putra, Raga Tetra (Universitas Muhammadiyah Magelang, 2024)
Hypertension during pregnancy, particularly preeclampsia and eclampsia, is a leading cause of maternal morbidity and mortality. Timely and appropriate management is crucial in preventing serious complications, including maternal death. This study aimed to describe the initial management of severe preeclampsia and eclampsia at RS PKU Muhammadiyah Palembang, Indonesia, during the period 2018–2021. This descriptive study employed a cross-sectional design. A total of 110 cases were randomly selected from medical records of patients diagnosed with severe preeclampsia and eclampsia. Data were analyzed based on the POGI 2016 guidelines. Among the 110 cases, 108 (98%) were diagnosed with severe preeclampsia, while 2 (2%) were cases of eclampsia. Of these, 65 patients (60.2%) received management that adhered to the POGI guidelines, whereas 43 patients (39.8%) did not. Both cases of eclampsia were managed in full compliance with the guidelines (100%). This study highlights that while the initial management of severe preeclampsia and eclampsia generally aligns with established standards, there remains room for improvement in procedural adherence. To further reduce maternal morbidity and mortality associated with these conditions, it is recommended that the hospital strengthen efforts to ensure full compliance with clinical guidelines. Keywords: Eclampsia; hypertension; initial treatment; mortality prevention; preeclampsia